Utilização do princípio do cross-check num conjunto de exames na avaliação audiológica infantil - Lima, Leydiane Castro de (2013)
Introduction: The development of early identification of hearing loss programs increases the number of children who need hearing assessment in a very early age. For this reason, there is the need to incorporate in the clinical routine a battery of audiological tests in order to assess hearing loss in different age groups. Objective: To describe the cross-check principle in a battery of tests proposed for infants and young children audiological evaluation; describe the subjects hearing tests results in a Hearing Care Service, and analyze the results of different tests when used together, according to the cross-check principle. Methods: This study was designed as descriptive, retrospective, qualitative and quantitative. A survey of the records of children enrolled in the diagnostic sector in the period August to December 2011, the audiological evaluation process. From a total of 62 records, we selected 30 that were in accordance with the selection criteria. Data analysis consisted of descriptive analysis and agreement by Kappa. Results: The age at the start of audiological diagnosis ranged from one to 44 months, with a mean of 17.8. There was a higher prevalence in the age group of 13 and 24 months (36.7%). In 50.1% of children, the diagnosis was completed in six weeks. When comparing the results of each test with the diagnostic conclusion, we observed that there was agreement in 64% of the results when compared with tympanometry, 92% with transient-evoked otoacoustic emissions stimulation with 100% Behavioral Audiometry and Brain-stem Auditory Evoked Potential. When analyzed together, there was strong agreement (kappa = 0.88) between the results of transient-evoked otoacoustic emissions and Behavioral Audiometry. In 92% of cases, otoacoustic emissions agreed with the results of Brainstem Auditory Evoked Potential. There was agreement in 100% of cases, compared with the Brain-stem Auditory Evoked Potential to Behavioral Audiometry. Conclusion: Behavioral Audiometry and Brain-stem Auditory Evoked Potential significantly agreed with the diagnosis. When the principle Cross-check within the set of tests was used, the transient-evoked otoacoustic emissions and Brain-stem Auditory Evoked Potential were most in agreement when analyzed with other tests. A battery of tests and the application of Principle Cross-check proved relevant in the assessment of children, having significant effects on the accuracy and reliability in the diagnosis of hearing loss